Penerapan Model Pembelajaran PJBL (Project Based Learning) Pada Kompetensi Perbaikan Sistem Pengapian Elektronik Untuk Meningkatkan Hasil Belajar Siswa XI TBSM Di SMKN 1 Mejayan Tahun Pelajaran 2018/2019 - Suherman, ali (GHAITSA : Islamic Education Journal, 2020)
Present day, learning at SMK Negeri 1 Mejayan tends to be teacher-centered learning, so students do not understand the learning material. In this study, researchers applied project-based learning so students could innovate about their learning outcomes. The method used in this study is an experimental method with a pre-post-test control group design. The population in this study were students of 11th-grade TBSM, there were two classes for those majoring in TBSM and the total population was 64 students. The sample used was 32 students of 11th grade TBSM 1 as an experimental class and 32 students of 11th grade TBSM 2 as a control class. Data collection using the learning outcome test, data analysis using t-test. The results of data analysis showed that in the control class the average learning outcomes in the pre-test reached (46.93) and after being given conventional learning methods increased to (73.17), so that in the control class after being given the conventional method an average increase reached (26.24) and in the experimental class the average learning outcomes in the pre-test reached (48.55) and after being given a project-based learning method increased to (80.14), so that in the experimental class after being given a project-based learning method increased by (31.59). Based on the results of the t-test the value of the post-test competency ignition system repair turns out there are differences in learning outcomes of ignition system improvement after using project-based learning methods